A STUDY ON THE IMPACT OF THE COVID-19 PANDEMIC ON THE SOCIAL ECONOMY IN KETANGGA VILLAGE, EAST LOMBOK, FROM AN ISLAMIC PERSPECTIVE - Marjan, Marjan (STAI Darul Kamal NW Kembang Kerang, 2024)
This research was motivated by Micro, Small and Medium Enterprises (MSMEs) in Ketangga Village, Suela District who were affected by the Covid-19 pandemic. This research method is qualitative research. The data sources used in this research are primary data and secondary data. In data collection techniques, researchers carried out observations, interviews and documentation. The results of this research show that the impact of the Covid-19 pandemic has resulted in disruption to the economy of Micro, Small and Medium Enterprises (MSMEs) in Ketangga Village, Suela District because since the Covid-19 pandemic, there have been many Micro, Small and Medium Enterprises (MSMEs) in Ketangga Village, Suela District. loss of buyers/customers. Not only does it have an impact on the economy, but it also has an impact on social life, including aspects of health and education. The health aspect highlights the large number of people who are sick but are reluctant to go to the doctor because they are afraid of being exposed to the Covid-19 virus. Meanwhile, from the educational aspect, namely the closure of schools after the Covid-19 pandemic, the face-to-face teaching and learning process is not allowed so it has to be done online.